Non‐24‐hour sleep‐wake disorder successfully treated with the combination of ramelteon and suvorexant in a case of autism spectrum disorder - Masaaki Iwata; Koichi Kaneko (Wiley, 2020)
Abstract Introduction Non‐24‐hour sleep‐wake disorder (N24SWD) is often observed in the visually impaired and those who isolate indoors. Melatonin receptor agonists may be used for treatment, but there is currently no evidence that they are effective in patients without visual impairment. Case We report a case of a 23‐year‐old woman who withdrew from her social life owing to autism spectrum disorder and experienced an unusual sleep rhythm. She presented with N24SWD. The N24SWD cycle averaged 25.6 days but was extended to 42 days using ramelteon. However, this was not enough. We prescribed the addition of suvorexant and the sleep cycle returned to normal. Conclusion N24SWD is a disease that seriously impairs social life and productivity. We propose a possible treatment strategy for N24SWD using ramelteon and suvorexant.